Uniting communities: harnessing social capital for community resilience during coronavirus disease 2019 - Alfitri, Alfitri; Taqwa, Ridhah; Budiyanto, Mumahammad Nur; Nadjib, Abdul; Santoso, Anang Dwi (International Journal of Public Health Science (IJPHS), 2024)
This research investigates the impact of both traditional and virtual social capital on community resilience, with engagement on social media as a mediating variable. The study surveyed 397 inhabitants of an urban sub-district in Palembang, Indonesia, and analyzed the data using the structural equation model partial least square (SEM-PLS) technique. The results indicate that it is critical to prioritize and activate various forms of social capital to enhance community resilience during the coronavirus disease 2019 (COVID-19) pandemic. The analysis showed that social media engagement had a significant positive impact on community resilience (p<0.05), however the influence of virtual bonding social capital was negligible and negatively skewed (p=0.084). It is significant to note that community resilience was significantly positively impacted by both traditional bonding and bridging social capital (both p<0.05). Social media involvement was also markedly positively impacted by virtual bonding and bridging social capital (both p<0.05). The link between virtual bonding, bridging social capital, and community resilience was strongly influenced by social media use in terms of mediation (both p<0.05). This emphasizes how important social capital, both physical and digital, and particularly social media participation, are to building community resilience during pandemics.